(untitled) (Advances in Systems Science and Applications, 2021)
An optimal algorithm for linear control of the unmanned vessel dynamic positioning system with provision for vessel characteristics, equipment, and the process has been developed. A block diagram for the automatic dynamic positioning system has been suggested which allows presenting a necessary set of devices for its technical implementation.